2012
DOI: 10.1038/bcj.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Risk-based classification of leukemia by cytogenetic and multiplex molecular methods: results from a multicenter validation study

Abstract: Modern management of leukemia and selection of optimal treatment approaches entails the analysis of multiple recurrent cytogenetic abnormalities with independent diagnostic or prognostic value. We report the first multicenter validation of a multiplex molecular assay for 12 relevant fusion transcripts relative to cytogenetic methods. Performance was evaluated using a set of 280 adult and pediatric acute or chronic leukemias representative of the variety of presentations and pre-analytical parameters encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The average negative probe signal in these experiments was 102 MFI with a maximum at 273 MFI and 95% of the signals between 0 and 177 MFI (data not shown). These results are in agreement with an independent limit of blank study showing that 95% of the signals generated in known negative samples are at least two-fold below 350 MFI for each probe (11). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The average negative probe signal in these experiments was 102 MFI with a maximum at 273 MFI and 95% of the signals between 0 and 177 MFI (data not shown). These results are in agreement with an independent limit of blank study showing that 95% of the signals generated in known negative samples are at least two-fold below 350 MFI for each probe (11). …”
Section: Discussionsupporting
confidence: 91%
“…By optimizing primers concentration and probes/amplicons length, every target in the original leukemia translocation panel was detected at about 1% cell line dilution or 2.E4 copies per RT reaction (Figure 1). This level of sensitivity, equivalent to the detection of one leukemia cell in a background of 100 normal cells, is superior to current clinical reference methods such as fluorescence in situ hybridization, Sanger sequencing or karyotyping (5 to 20%) and was shown to be adequate for the characterization of leukemia samples at diagnosis (11,12). Using an optimized RT system and PCR buffer (see Materials and Method) we demonstrated that the multiplex assay system can be further enhanced to reach 0.1 to 0.01% dilution or 2.E3 copies per RT reaction.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations